Sucessão geracional no meio rural: percepção dos filhos em relação aos estilos parentais - Boscardin, Mariele (2024)
Generational succession refers to a multifaceted process, demonstrating that there are different factors that can positively or negatively influence the choice of potential successors. Such factors range from structural aspects of properties and the rural environment to family and emotional aspects, the latter being recurrent in different contexts, largely because the lack of dialogue between parents and potential successors can negatively influence generational succession. An approach, not yet studied, that can help in understanding these processes is the parental styles approach. The concept of parental styles refers to a set of attitudes present in relationships between parents and children. This is a typology initially proposed by Baumrind (1966) that has been widely studied, especially in the field of psychology. The author developed a model, where she defines three main parenting styles: authoritarian, authoritative and permissive. Later, Maccoby and Martin (1983) reorganized this classification through the dimensions of Demandingness and Responsiveness, dividing the permissive style into indulgent and negligent. In this sense, parental styles began to be classified according to these two dimensions. Starting to be identified and systematized as authoritarian, authoritative, indulgent and negligent. The objective of this study was to evaluate the relationship between generational succession in rural areas and parental styles. To meet the proposed objective, a study was carried out with 252 potential successors from the state of Rio Grande do Sul. To reach the respondents, the snowball sampling method was used, which allows the sample to be created by people who share or know of other people who have the characteristics defined for the application of the questionnaire. To constitute the sample, the recommendations of Hair et al. were adopted. (2009) who recommends that the researcher consider at least five times the number of observations for an item to be evaluated. The data collection instrument was composed of open and closed questions and consisted of three parts: I) Questions related to sociodemographic variables of the potential successor and rural properties; II) Issues related to generational succession and III) Issues related to parental styles. This third instrument was developed, tested and validated. After data collection, the data was organized and analyzed. The IBM Software Statistical Package for Social Science (SPSS), SAS Analytics Software and Microsoft Excel were used. The results obtained through Croanbach's Alpha attested to the validity of the instrument for the perception of potential successors in relation to parental styles. Furthermore, it was found among respondents that most perceive their parents as authoritative (40.08%) and indulgent (36.90%). The analysis based on the ordinal logistic regression model also demonstrated that the variables sex of the potential successor, father's age, hours dedicated to farm activities, socialization/insertion in agricultural activities and parental style were significant considering the chance of the interviewee answering higher values score on whether to consider yourself a successor. Regarding parenting styles, differences were observed between the authoritative style vs. authoritarian style with 4.321 times more chance of higher score values for the authoritative style. Significant values were also found between the authoritarian style vs. indulgent style with 83% less chance of higher score values for the authoritarian style. Finally, multivariate analysis made it possible to identify 14 variables responsible for differentiating the four parental styles. Four of them are related to the Demand dimension and six are related to Responsiveness. In addition to these, four other variables were significant in differentiating between groups, including dialogue with parents, age of the potential successor, encouragement and recognition in relation to being a farmer and time of experience in agricultural activities. It was also observed that the variable “E5- Required me to participate in agricultural activities without participating in the income” is the most important variable to differentiate the groups. Furthermore, authoritative and indulgent parenting styles have a high relationship with male respondents. Meanwhile, the authoritarian style is associated with females and respondents with higher education. Another aspect is that predominantly authoritative and indulgent parenting styles have more similar characteristics to each other, while authoritarian and negligent styles also have greater similarities. In general, it is concluded that among potential successors, the authoritative parental style is related to a greater probability of generational succession in properties.